Analisa Biaya Penyaluran Pupuk Urea Bersubsidi Dengan Menggunakan Metode Stepping Stone Di Kabupaten Aceh Besar - Sayid Insya Mustafa (Puslatbang KHAN, 2018)
The purpose of this study is to determine whether the subsidized urea fertilizer distribution system in the district of Aceh Besar is efficient or not. In the distribution of subsidized urea fertilizer, the responsible institution is state- owned company namely PT. Pupuk Sriwijaya, and for the district of Aceh Besar, by PT. Pupuk Sriwijaya, has appointed three distriutors, namely PT. Karya Pelita Makmur, CV. Leubok Joek Jaya and Puskud Aceh. The distributors obtain their distribution areas. PT. Karya Pelita Makmur distribute urea fertilizers as much seven districts, CV. Leubok Joek Jaya for six districts and also Puskud Aceh for five districts. After the calculation, the cost of transportation carried to by three distirbutors is not efficient. The method used in this calculation is calculation tabel of North West Corner (NWC).